2015
DOI: 10.1002/btpr.2210
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the dynamic packing behavior of preparative chromatography columns via discrete particle modeling

Abstract: Preparative packed-bed chromatography using polymer-based, compressible, porous resins is a powerful method for purification of macromolecular bioproducts. During operation, a complex, hysteretic, thus, history-dependent packed bed behavior is often observed but theoretical understanding of the causes is limited. Therefore, a rigorous modeling approach of the chromatography column on the particle scale has been made which takes into account interparticle micromechanics and fluid-particle interactions for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It is well-known that such materials interact dissipatedly through inelastic collisions and a network of frictional force-chains which influence bed formation and long-term bed stability. 23,24 This was observed during the study of the influence of particle friction during the packing of two particle types with distinct and different levels of surface roughness. It was observed that smooth particles with lower friction slipped more readily during packing, resulting in a denser, albeit more inhomogeneous, microstructure.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…It is well-known that such materials interact dissipatedly through inelastic collisions and a network of frictional force-chains which influence bed formation and long-term bed stability. 23,24 This was observed during the study of the influence of particle friction during the packing of two particle types with distinct and different levels of surface roughness. It was observed that smooth particles with lower friction slipped more readily during packing, resulting in a denser, albeit more inhomogeneous, microstructure.…”
Section: Introductionmentioning
confidence: 92%
“…The 3D reconstruction of real packings enables the geometric analysis of their structure 20,21 or their use in posterior computer simulations. 22 Additionally, granular simulations of in silico generated packings permit the study of events difficult to access in real packings, 23 thus enabling the study of timedependent processes such as structure evolution under operation or particle migration. Among several works following this approach, 6,13 the effect of the slurry concentration during packing on the bed structure and efficiency was studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such deformation can be expected because column packing typically involves linear flow rates of up to 7 m h −1 (Boi et al, 2020), which compress the resin particles beyond the point achieved by gravity settlement alone, typically by a factor of 1.15 for synthetic polymer resins (e.g., based on methacrylic polymers) that are considered to be semi-rigid (Baru 2003;Lee et al, 2015;Gebauer and Tschöp 2018). Although such packing stabilizes the chromatography bed (Dorn et al, 2017), it occurs predominantly at the inlet and outlet of the column (Dorn and Hekmat 2016;Dorn et al, 2017), thus distorting the flow regime Frontiers in Bioengineering and Biotechnology frontiersin.org in these regions. The analysis of fluid dynamics in packed beds can account for some degree of resin particle polydispersity (Shalliker et al, 2002;Püttmann et al, 2014) but the nonspherical shapes caused by dense packing are generally not considered (Bouhid de Aguiar et al, 2017).…”
Section: Resin Packing and Wall Effectsmentioning
confidence: 99%
“…Therefore, the complexity of the particle morphology become one major restriction for the rapid modelling of an urgent problem. In the previous study, the spherical assumption was widely adopted to simulate the particle redistribution in general [ 10 ], and discussion has extended to other regular-shaped particles, including column [ 11 ], elliptic [ 12 ] and polygon [ 13 ]. MD solution also adopted the spherical assumption, but intermolecular bonding was introduced [ 14 ].…”
Section: Introductionmentioning
confidence: 99%